EKSEKUSI HAK TANGGUNGAN ATAS TANAH DAN BANGUNAN DI BANK PEMBIAYAAN RAKYAT SYARIAH âBANGUN DRAJAT WARGAâ DI DAERAH ISTIMEWA YOGYAKARTA - , Bena Kuzarito, Kunthoro Basuki, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research objectives of the Implementation of Execution Mortgage on Land and Buildings in Bank Pembiayaan Rakyat Syariah âBangun Drajat Wargaâ in Yogyakarta conducted to determine: 1) How does the execution of the object Mortgage of land and buildings at PT. BPRS BDW in Yogyakarta 2) What are the advantages and constraints can be obtained from the execution of a Mortgage at PT. BPRS BDW in Yogyakarta. This research method is yuridis empiris which are juridical studies to obtain primary data through interviews with informant and respondent, to support the primary data do library research to obtain secondary data, the data obtained and analyzed qualitatively and by the results descriptively. The results can be stated that 1) The execution of the object Mortgage Land and Buildings in PT. BPRS BDW city of Yogyakarta performed with 2 (two) ways, namely through a sale under a completely hand made by the debtor, and the second way is through a public tender is entirely the responsibility of from creditor through the intermediary Auction Officials Class I at KPKNL, city of Yogyakarta. 2) While the advantages and constraints of the execution of a Mortgage in Yogyakarta in sales under the hands of the banks do not bother to sell the Mortgage object that have been agreed in the financing agreement for the sale process has been carried out by the debtor, while at a public auction that advantage is price competitive and transparent as an auction conducted by government officials, namely Auction Officials Class I. Constraints of the implementation of the execution of Mortgage is that if the object is still occupied by relatives or any third party (tenant), it takes a long time and no small cost to clear the object Mortgage and Mortgage objects there is a tendency that is still inhabited the not sold to be sold in public auction.